The effects of anthropogenic pollution on the Kanev Reservoir (Ukraine) phytoplankton. 1. Phytoplankton dynamics at stations with different levels of pollution - Mikhailyuk, T.I.; Kamenir, Y.; Popova, A.F.; Kemp, R.B.; Dubinsky, Z. (Інститут ботаніки ім. М.Г. Холодного НАН України, 2008)
The aim of the investigation was to compare the phytoplankton structure in two zones of the river part of Kanev Reservoir characterized by different levels of urban pollution. Two stations were selected for this purpose: 1, in a relatively pure area of the the river part of Kanev Reservoir; and 2, at the mouth of the Dneiper tributary, the Syrets River, which has been polluted by mineral and organic substances from urban sewage. The “vibrancy” of the phytoplankton was evaluated by determining their biomass, cell abundance, and cell surface area (denoted as B, N, and S, respectively), achieved on the basis of a routine monitoring dataset collected over 24 months at these stations. The investigated zones were characterized by divergent phytoplankton composition and considerably different annual dynamics. The profiles shown by the B, N and S dynamics of the phytoplankton at station 1 were characterized by regular and predictable peaks in summer, formed by the same complex of algal species. Similar-type graphs for station 2 exhibited 3-4 peaks per year formed by completely different groups of algae during different periods. Furthermore, the saprobic zone indicator species, as well as those characterized by highly specific cell-surface estimates, were often observed at station 2. Such species were absent or developed only to a minor extent in phytoplankton of station 1. These facts can be interpreted as symptoms of ecosystem destabilization at station 2, which could be due to the impact of polluted water from the Syrets River on the phytoplankton of the Kanev Reservoir.